The Queen Of Uzbek Theatre - Murodov Halim; Rajabova Jamila (International Journal Of History And Political Sciences, 2025)
By the mid-20th century, women in Uzbekistan had undergone their own stages of development in the field of arts. During this period, many women participated in creating stage works for adults and children that could serve as examples, as well as in dramaturgy and the art of acting. These women made a major contribution to the preservation and development of art through their creative works zand theatrical performances, and through their active roles in education and upbringing processes they significantly contributed to the development of our national culture. This article historically highlights the life and work of Ma’suma Qoriyeva, one of the women active in the arts in Uzbekistan, and the aspects of her legacy that can serve as an example for today’s women.